Relationship between brain structure and Cerebral Visual Impairment in children with Cerebral Palsy: A systematic review. (April 2020) - Philip, Swetha Sara; Guzzetta, Andrea; Chorna, Olena; Gole, Glen; Boyd, Roslyn N.
Highlights: Periventricular leucomalacia was the most commonly reported brain lesion associated CVI in children with CP. The role of brain structures such as grey matter and subcortical structures in CVI and CP is largely unknown. Current evidence associating different patterns of CVI with motor types of CP and structural and functional MRI is weak. There is a need for uniform reporting of both brain structure/function and CVI classification to help further understanding of CVI. Abstract: Background: Cerebral Visual Impairment (CVI) is very common yet often unrecognised visual dysfunction in children with Cerebral Palsy (CP). Magnetic Resonance Imaging (MRI) is the diagnostic tool in the investigation of brain lesions in children with CP and CVI. Aim: The aim of this systematic review is to evaluate the relationship between brain structure and CVI, as determined by MRI in children with CP. Methods and procedures: A comprehensive search of 5 database (PubMed, EMBASE, SCOPUS, CINAHL and Cochrane Database) was undertaken up until June 2019. The PRISMA checklist was then utilised to report on the process of selecting eligible papers. A total of 30 observational studies met the full inclusion criteria. Further, STROBE checklist was employed to report on the observational studies. Outcomes and results: Periventricular leucomalacia on MRI was found to have a strong association with CVI in all 30 studies. Only 13 (43 %) studies described dorsal and/ ventral stream dysfunction. There was ambiguity in the definition of CVI. Conclusions and implications: The overall level of evidence correlating different patterns of CVI and CP (based on GMFCS, motor type and distribution) and MRI was low. Further studies utilising advances in MRI are needed to understand brain reorganisation and patterns of CVI and suggest rehabilitation therapy inclusive of vision.